Desempenho de alface roxa (lactuca sativa l.) em resposta a diferentes doses de esterco bovino, cultivada em garrafas pet. - Araujo, Julyanner Leite Mélo Regis de. (2017)
Lettuce (Lactuca sativa L.) is one of the most popular vegetables planted and consumed in the world. With growing population awareness about environmental preservation, polyethylene terephthalate (PET) bottles have been used increasingly for vegetables cultivation, especially lettuce. The objective of this research was to evaluate the performance of lettuce 'Roxa' fertilized with different doses of bovine manure produced in PET bottles. The experiment was conducted at Sítio Almeida, Lagoa Seca, PB, Brazil, in a completely randomized design, containing the following treatments with bovine manure: T1: 0% (control); T2: 25%; T3: 50%; T4: 75%, each one with five replicates. The following parameters were evaluated twenty five days after seedlings transplanting: plant height, diameter of upper part of plants, number of leaves, stem height, fresh and dry matter of aerial part, main root diameter, main root length, root fresh matter and root dry matter. These measurements were made using a graduated ruler, digital calliper and analytical balance. After fresh plants measuring, vegetal matter was packed in paper bags, which were properly identified and conducted to a forced air circulation oven at 65°C during 72 hours. The best treatment was 75% of bovine manure. At 25% of bovine manure, generally "Purple" lettuce production decrease in relation to the control. It is suggested in this case do not use fertilization, because the production only start from higher doses than 25% of bovine manure. There was no significant effect (p> 0.05) of bovine manure rates on the gas exchanges of “Purple” lettuce plants produced in Luvisol. However, unfolding degrees of freedom of doses into linear regression, the mean of transpiration (E) and stomatal conductance (gs) were adjusted to the linear model with decreasing behavior and high predictive capacity of the models. Using horizontal PET bottle model did not prove to be efficient on expanding “Purple” lettuce roots, since both the main and adventitious roots were concentrated only in the central part of the bottle, thus failing to receive nutrients of substrate present on the sides of the bottle.